Automating Crisis Communication in Public Institutions–Towards Ethical Conversational Agents That Support Trust Management - Hofeditz, Lennart; Mirbabaie, Milad; Erle, Lukas; Knoßalla, Eileen; Timm, Lara (Proceedings of the 17th International Conference on Wirtschaftsinformatik)

Credibility of Cyber Threat Communication on Twitter–Expert Evaluation of Indicators for Automated Credibility Assessment - Basyurt, Ali Sercan; Fromm, Jennifer; Stieglitz, Stefan; Mirbabaie, Milad (Proceedings of the 17th International Conference on Wirtschaftsinformatik)

From Dark Patterns to Digital Sludging–Mapping the Ethical Debate on Controversial Persuasive System Design - Clausen, Sünje; Marx, Julian; Mirbabaie, Milad; Stieglitz, Stefan (Proceedings of the 43rd International Conference on Information Systems (ICIS))

Knowledge Work ‘Unplugged’-Digital Detox Effects on ICT Demands, Job Performance and Satisfaction - Mirbabaie, Milad; Braun, Lea-Marie; Marx, Julian (Proceedings of the 17th International Conference on Wirtschaftsinformatik)

Motivators of Knowledge Workers to Conduct Digital Detox - Marx, Julian; Braun, Lea Marie; Mirbabaie, Milad (Proceedings of the 43rd In the Proceedings of the 43rd International Conference on Information Systems (ICIS))

‘Botfluencers’–The Impact of Social Bot Awareness and User Personality on Brand Opinion Formation - Brünker, Felix; Marx, Julian; Mirbabaie, Milad; Stieglitz, Stefan (Proceedings of the Australasian Conference on Information Systems (forthcoming))

Working with ELSA – How an Emotional Support Agent Builds Trust in Virtual Teams - Hofeditz, Lennart; Harbring, Mareen; Mirbabaie, Milad; Stieglitz, Stefan (Proceedings of the Annual Hawaii International Conference on System Sciences)

SMART-Portal: A data tracking tool for research purposes from social media and news websites - Stieglitz, Stefan; Basyurt, Ali; Mirbabaie, Milad (Proceedings of the Annual Hawaii International Conference on System Sciences)

Oiling the ’Tireless Selling-Machine’ - Exploring Requirements for the Deployment of Social Bots in Social Commerce - Brünker, Felix; Marx, Julian; Mirbabaie, Milad; Stieglitz, Stefan (55th Hawaii International Conference on System Sciences, HICSS 2022, Virtual Event / Maui, Hawaii, USA, January 4-7, 2022)

Help Wanted-Challenges in Data Collection, Analysis and Communication of Cyber Threats in Security Operation Centers - Basyurt, Ali Sercan; Fromm, Jennifer; Kuehn, Philipp; Kaufhold, Marc-André; Mirbabaie, Milad (Proceedings of the 17th International Conference on Wirtschaftsinformatik)

Ethics Guidelines for Using AI-based Algorithms in Recruiting: Learnings from a Systematic Literature Review. - Hofeditz, Lennart; Mirbabaie, Milad; Luther, Audrey; Mauth, Riccarda; Rentemeister, Ina (HICSS)

Man nehme... den Konjunktiv. Verbformen in Kochrezepten - Wallmeier, Nadine (Praxis Deutsch)

„Alles Leben ist Problemlösen“ (Popper) – Die Komplexität der alltäglichen Lebensführung erfassen durch Problembasiertes Lernen - Bigga, Regine; Raacke, Georg (HiBiFo – Haushalt in Bildung & Forschung)
In der Haushaltswissenschaft und der haushaltsbezogenen Bildung besteht eine große Herausforderung darin, Komplexität zu erfassen, zu verstehen und als eine bewältigbare Aufgabe anzunehmen. Problembasiertes Lernen (PBL) bietet ein Konzept, komplexere Frageund Problemstellungen aus der alltäglichen Lebensführung und deren Verwobenheit mit gesellschaftlichen Rahmenbedingungen zu verstehen. Aus hochschuldidaktischer Sicht werden Chancen und Begrenzungen diskutiert.

Ressourcen – Gesundheit zwischen Eigenverantwortung und gesellschaftlicher Verantwortung - Bigga, Regine (HiBiFo – Haushalt in Bildung & Forschung)
Die Herstellung und Aufrechterhaltung von Gesundheit und Wohlergehen wird in vielen Diskursen als alleinige Aufgabe des Individuums angesehen. Die Ressource Gesundheit hängt vom individuellem Verhalten ab, aber auch von gesellschaftlichen Rahmenbedingungen. Es wird der Frage nachgegangen, welche äußeren Bedingungen sich negativ oder positiv auf die Bildung der Ressource Gesundheit auswirken.

Neuronale Netze in der Konstruktion zur Ausschöpfung der Potentiale additiver Fertigungstechnologien - Ott, Manuel; Meihöfener, Niclas; Koch, Rainer (Bericht 407 - 7. Tagung des DVM-Arbeitskreises Additiv gefertigte Bauteile und Strukturen)
Die additive Fertigung bietet die Möglichkeit, digitale Prototypen dank der Besonderheit der werkzeuglosen Fertigung schnellstmöglich in reale Strukturen umzusetzen. Dieses Verfahren kann jedoch nur dann mit optimaler Geschwindigkeit genutzt werden, wenn Engpässe wirksam vermieden werden können. Einer dieser Engpässe ist der Konstruktionsprozess. Gerade im Bereich der additiven Fertigung sind in letzter Zeit immer leistungsfähigere Softwarelösungen erschienen, die das Design für die additive Fertigung, einschließlich der meisten Computer-Aided-Design (CAD)-Aufgaben, beschleunigen. In vielen Bereichen wird daher bereits versucht, so viele Schritte wie möglich zu automatisieren, nicht selten unter Verwendung neuronaler Netze und künstlicher Intelligenz. Dieser Beitrag zeigt am Beispiel einer automatisierten Strukturoptimierung eines Stuhls, warum das Nutzen neuronaler Netze im Konstruktionsprozess sinnvoll ist, um die Bereiche der konventionellen Topologieoptimierung und des Generative Design weiter zu verknüpfen und somit die Produktentwicklungszeit zu reduzieren.
Keywords: Künstliche Intelligenz; Neuronale Netze; 3D-Druck; Design for Additive Manufacturing

The environmental impact on the strain rate dependent energy absorption capability of a hybrid crash absorber element - Haller, Sebastian; Tinkloh, Steffen Rainer; Tröster, Thomas; Brandt, Robert (5th International Conference Hybrid 2022 Material & Structures)

Konturen einer praxistheorethischen Professions- und Entscheidungsforschung - Dahmen, Stephan (Empirische Pädagogik)
Ausgehend von der Problematisierung eines individualistischen Begriffs von Entscheidung referiert der Beitrag eine praxistheoretische Perspektive auf Entscheidungen in pädagogischen Kontexten mit dem Zweck, die Sensitivität für deren empirische Erforschung, insbesondere im Rahmen qualitativ-rekonstruktiver Forschung zu erhöhen. Die praxistheoretische Perspektive auf Soziale Wirklichkeit wird anhand von drei perspektivischen Verschiebungen des Entscheidungsbegriffs diskutiert: Erstens, der Frage der raum-zeitlichen Verortung und Beobachtbarkeit von Entscheidungen, zweitens, der praxistheoretischen Dezentrierung des Entscheidungs- und Handlungssubjekts und drittens, anhand der Frage der Rationalität von Entscheidungen. Der Beitrag argumentiert diesbezüglich für eine analytische Abkehr von präskriptiven Modellen professionellen Entscheidens als reflexiv-intentionale Verknüpfung von Diagnose, Inferenz und Behandlung und plädiert dafür, den Untersuchungsfokus vom individuellen Akteur zum situierten, prozesshaften Vollzug von Handlungen in ausgestatteten, formatierten und vernetzten Situationen zu verschieben.

Toward a Competence Model for Graphical Modeling - Soyka, Chantal; Schaper, Niclas; Bender, Elena; Striewe, Michael; Ullrich, Meike (ACM Transactions on Computing Education)
Modeling is an integral part of many computing-related disciplines and thus also represents a curricular core component in computing education in tertiary education. Competence models in which modeling is integrated at least to some extent already exist in some of these disciplines. However, for the core component of graphical modeling, a competence model that illuminates the relevant competences in detail is still lacking. Therefore, we develop a competence model for graphical modeling with the aim to make teaching and especially assessments in the field more competence-oriented. This paper reports on the first two studies conducted to develop and validate the competence model for graphical modeling. In the first study, the structure of the competence model was developed based on theories and approaches of educational science. Competences relevant for graphical modeling were deductively derived from literature and existing university course descriptions using techniques of qualitative content analysis. The result of the first study is a preliminary competence model. In the second study, the preliminary competence model was reviewed by means of an expert rating in the modeling community. The competence model was revised and refined based on these findings and subsequent expert discussions. The main result of the investigation represents the competence model for graphical modeling (CMGM), which includes a total of 74 competence facets at different cognitive process levels in the five content areas of ”model understanding and interpreting”, ”model building and modifying”, ”values, attitudes, and beliefs”, ”metacognitive knowledge and skills”, and ”social-communicative skills”.
Keywords: graphical modeling; conceptual modeling; computer science; competence model; higher education

Piloteinsatz einer E-Assessment-Plattform für die grafische Modellierung - Ullrich, Meike; Pfeiffer, Peter; Schiefer, Gunther; Soyka, Chantal; Stottrop, Tobias; Striewe, Michael; Fettke, Peter; Loos, Peter; Oberweis, Andreas; Schaper, Niclas (20. Fachtagung Bildungstechnologien (DELFI))

E-Assessment-Plattform für die grafische Modellierung - Ullrich, Meike; Pfeiffer, Peter; Schiefer, Gunther; Soyka, Chantal; Stottrop, Tobias; Striewe, Michael; Fettke, Peter; Loos, Peter; Oberweis, Andreas; Schaper, Niclas (20. Fachtagung Bildungstechnologien (DELFI))